Putting the human at the centre: Human rights and literary studies in South Africa - Ndlovu, T. (South African Journal of Higher Education, 2019)
Drawing on my teaching experience of Human Rights and African Literature, particularly the unpacking of “human” in human rights, this paper argues for revitalising and deepening the study of literature in South African universities, with the aim of reconstructing and (re)humanising societies. Through focalising the imbrication of story/narrative with the human and rights, the article uses specific lecture/class room experiences to suggest another way of reframing enduring historic modes of perception, some of which tend to the inhumane or “monstrous”. Given its emphasis on basic human rights such as dignity, equality and freedom, rights-reading coupled with a reflexive methodology to the teaching and learning of literature, can contribute to an informed citizenry. The paper suggests that such approaches point to the future of literary scholarship – interventionist and interdisciplinary.